Study aimed to identify the effect of Work incidents on the Worker Personality through the Motivation for Professional achievement index in one of Algerian Industrial company E.N.I.C.A.B - doubbakh, Kouider (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2022)
This study aimed to identify the effect of work incidents on the worker personality through the Burnout index in one of Algerian industry enterprises (E.N.I.C.A.B), and that was by comparing the Burnout level in samples of moderate injured and uninjured workers. In order to solve this problem and control it on field; we have chosen the company of prodicing cable in biskra(E.N.IC.A. B) as a placé to make a field study. To test the hypothesis of this study; any techniques have been taken to gather data, those techniques were designing questionnaire and destribut them on the research sample. addition to relying on interviews with some workers, as well as the official in charge of prevention and industrial security in the establishment, observation was also relied upon.By following the steps of the descriptive analytical approach, the obtained information was collected, classified and processed statistically to test the research hypotheses, and all hypotheses were verified. The result was an existence of differences due to injury feedback to the absence of the psychologist within industrial security committees and the absence of provide for psychological injured workers returning to practice their work after taking a break of rest and treatment.